2001
DOI: 10.1073/pnas.171304098
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of plant growth by cytokinin

Abstract: Cytokinins are a class of plant-specific hormones that play a central role during the cell cycle and influence numerous developmental programs. Because of the lack of biosynthetic and signaling mutants, the regulatory roles of cytokinins are not well understood. We genetically engineered cytokinin oxidase expression in transgenic tobacco plants to reduce their endogenous cytokinin content. Cytokinin-deficient plants developed stunted shoots with smaller apical meristems. The plastochrone was prolonged, and lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

42
730
4
23

Year Published

2003
2003
2017
2017

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 954 publications
(799 citation statements)
references
References 35 publications
42
730
4
23
Order By: Relevance
“…In a previous study, we showed that overexpression of AtCKX genes in transgenic tobacco plants reduces the endogenous cytokinin content and profoundly influences root and shoot development (Werner et al, 2001). Here, we report the functional analysis of six gene family members in the model plant Arabidopsis.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…In a previous study, we showed that overexpression of AtCKX genes in transgenic tobacco plants reduces the endogenous cytokinin content and profoundly influences root and shoot development (Werner et al, 2001). Here, we report the functional analysis of six gene family members in the model plant Arabidopsis.…”
Section: Introductionmentioning
confidence: 85%
“…Genes that encode enzymes that catalyze cytokinin breakdown have been isolated from maize (Houba-Hérin et al, 1999;Morris et al, 1999), Arabidopsis (Bilyeu et al, 2001;Werner et al, 2001), and orchids (Yang et al, 2003). The Arabidopsis AtCKX gene family has seven members ( AtCKX1 to AtCKX7 ) (for review, see Schmülling et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Cytokinins appear to interact with auxins antagonistically in a number of developmental processes such as to promote the release of axillary buds from dormancy and to suppress lateral root formation (Werner et al, 2001). They are synthesised in root tips (Chiappetta et al, 2001;Sossountov et al, 1988), and might be expected to limit the level of EXO expression in the meristem, since Northern analysis showed downregulation of EXO transcription by cytokinins.…”
Section: Regulation By Hormonesmentioning
confidence: 99%
“…The use of synthetic cytokinins (BAP or TDZ) is advantageous not only because they promote shoot induction, but also because they are immune to degradation by cytokinin oxidase, thereby increasing the effectiveness of the pretreatment (Werner et al 2001). Reports on Curcuma longa and Curculigo orchioides show that explants obtained from seedlings germinated in the presence of TDZ are more responsive in shoot regeneration than explants with no treatment (Prathanturarug et al 2005, Thomas 2007).…”
Section: Cytokinin Pretreatment Relevancementioning
confidence: 99%
“…Finally, cytokinins play a central role during the cell cycle and influence numerous developmental processes, including the formation of shoot meristems, demonstrating their function beyond maintaining the cell cycle (Werner et al 2001).…”
Section: Cytokinin Pretreatment Relevancementioning
confidence: 99%